57.6k views
20 votes
Substitute equation (2) into (1) to give a new equation for p that involves only I and R

Re arrange (2) to make I the subject, and substitute your result into equation (1) to give a new equation containing only V and R

Substitute equation (2) into (1) to give a new equation for p that involves only I-example-1
User Cfg
by
5.7k points

1 Answer

11 votes

Answer:


p = {i}^(2) r


i = \sqrt{ (p)/(r) }

P= VI

V= IR

Substitute eqn 1 into eqn 2

P= (IR) I


p = {i}^(2) r


(p)/(r) = \frac{ {i}^(2)r }{r}


{i}^(2) = (p)/(r)


i = \sqrt{ (p)/(r) }

User Flo Doe
by
5.6k points